Psalm 39 and its place in the development of a doctrine of retribution in the Hebre Bible - Botha, Phil J. (Old Testament essays, 2017)
Psalm 39 is a peculiar, late post-exilic wisdom composition which reflects the style of a supplication of a sick person, but actually rather constitutes a meditation on the transitoriness of human life. It has been neatly integrated into the conclusion of Book I of the Psalter by a late post-exilic redaction, but displays antithetic views with regard to expectations about retribution expressed in other psalms ostensibly from the same post-exilic era. This article explores its possible purpose in view of its form, its integration into Book I of the Psalter, and particularly its seeming contrastive stance towards Pss 34 and 37. Its apparent criticism of the perspective on retribution expressed in other wisdom psalms renders it very similar to Ps 73 as well as to notions expressed in the Book of Job, and the psalm is therefore compared to these texts as well.